2018
DOI: 10.1016/j.envres.2018.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Ozone, NO2 and PM10 are associated with the occurrence of multiple sclerosis relapses. Evidence from seasonal multi-pollutant analyses

Abstract: Background Triggers of multiple sclerosis (MS) relapses are essentially unknown. PM10 exposure has recently been associated with an increased risk of relapses. Objectives We further explore the short-term associations between PM10, NO2, benzene (C6H6), O3, and CO exposures, and the odds of MS relapses’ occurrence. Methods Using a case-crossover design, we studied 424 MS patients living in the Strasbourg area, France between 2000 and 2009 (1783 relapses in total). Control days were chosen to be±35 days rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 44 publications
3
39
1
Order By: Relevance
“…Exposure to air pollutants initiates pathological processes in MS and leads to cerebral autoimmunity through inflammatory-oxidative cascades, loss of immunological tolerance, and neurodegeneration [ 187 ]. NO2, O3, and PM10 are associated with the appearance of MS relapses [ 188 ]. In fact, PM10 contributes to MS relapses through oxidative stress mechanisms [ 189 ].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Exposure to air pollutants initiates pathological processes in MS and leads to cerebral autoimmunity through inflammatory-oxidative cascades, loss of immunological tolerance, and neurodegeneration [ 187 ]. NO2, O3, and PM10 are associated with the appearance of MS relapses [ 188 ]. In fact, PM10 contributes to MS relapses through oxidative stress mechanisms [ 189 ].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…In a recent study, we have established a significant association between air-borne particulate matter levels and inflammatory activity of the disease, as expressed by the presence of gadoliniumenhancing lesions on brain MRI in MS patients (9). Other groups have also observed an association between ambient levels of air pollution and MS prevalence (10), as well as clinical activity of the disease (11)(12)(13)(14).…”
mentioning
confidence: 81%
“…A few studies have shown an association between PM 10 levels and risk of MS relapse or MRI activity . A deeper look at various pollutants suggested an increased risk of MS relapse following recent exposure to nitrogen dioxide (particularly during the cold season) or ozone (particularly for the hot season) . Benzene and carbon monoxide were not associated with MS relapses.…”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 99%